Potential of Myrtus communis Linn. as a bifunctional food: Dual high-resolution PTP1B and α-glucosidase inhibition profiling combined with HPLC-HRMS and NMR for identification of antidiabetic triterpenoids and phloroglucinol derivatives. (January 2020) - Liang, Chao; Staerk, Dan; Kongstad, Kenneth T.
Graphical abstract: Highlights: Myrtus communis holds potential as bifunctional food for management of type-2-diabetes. High-resolution bioactivity profiling performed against α-glucosdase and PTP1B. Fourteen active triterpenoids and three phloroglucinol derivatives characterized. Three new phloroglucinol derivatives isolated and identified. Abstract: Myrtus communis Linn., an aromatic shrub widely distributed in Mediterranean littoral, is traditionally used as a culinary herb and for manufacturing of the local Sardinian liquor, Mirto. In this study, the potential for developing M. communis into a functional food to treat type-2-diabetes (T2D) was investigated. Antidiabetic constituents in crude defatted chloroform extract of M. communis were pinpointed by dual high-resolution PTP1B and α-glucosidase inhibition profiling. Subsequent analytical-scale HPLC separation led to isolation and identification of 14 triterpenoids and three phloroglucinol derivatives associated with PTP1B and/or α-glucosidase inhibitory activity with IC50 values in the range of 8.9–69.4 μm and 34.3–88.5 μm, respectively. We also report three previously undescribed phloroglucinol derivatives. This is the first report of PTP1B inhibitors in M. communis, and the identification of both PTP1B and α-glucosidase inhibitors, demonstrates the potential of M. communis as a bifunctional food for management of T2D.